2015
DOI: 10.3390/md13052890
|View full text |Cite
|
Sign up to set email alerts
|

Alginate Hydrogels Coated with Chitosan for Wound Dressing

Abstract: In this work, a coating of chitosan onto alginate hydrogels was realized using the water-soluble hydrochloride form of chitosan (CH-Cl), with the dual purpose of imparting antibacterial activity and delaying the release of hydrophilic molecules from the alginate matrix. Alginate hydrogels with different calcium contents were prepared by the internal setting method and coated by immersion in a CH-Cl solution. Structural analysis by cryo-scanning electron microscopy was carried out to highlight morphological alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(97 citation statements)
references
References 42 publications
2
94
0
1
Order By: Relevance
“…274 As for the polymers composed mainly of CS, semi-interpenetrating CMCh/poly(acrylonitrile) hydrogels were reported to have clearly better antibacterial activity with more CMCh, and hydrogel coating by electrophoretic co-deposition of CS/alkynyl CS exhibited better antibacterial activities than pure CS hydrogel. 19,275 In the study by Straccia et al, 276 alginate hydrogels coated with CS hydrochloride showed intrinsic antimicrobial activity against E. coli. Quaternary ammonium CS/PVA/polyethylene oxide (PEO) hydrogels were reported to exhibit a pronounced inhibitory effect against S. aureus and E. coli.…”
Section: Antimicrobial Polysaccharidesmentioning
confidence: 99%
“…274 As for the polymers composed mainly of CS, semi-interpenetrating CMCh/poly(acrylonitrile) hydrogels were reported to have clearly better antibacterial activity with more CMCh, and hydrogel coating by electrophoretic co-deposition of CS/alkynyl CS exhibited better antibacterial activities than pure CS hydrogel. 19,275 In the study by Straccia et al, 276 alginate hydrogels coated with CS hydrochloride showed intrinsic antimicrobial activity against E. coli. Quaternary ammonium CS/PVA/polyethylene oxide (PEO) hydrogels were reported to exhibit a pronounced inhibitory effect against S. aureus and E. coli.…”
Section: Antimicrobial Polysaccharidesmentioning
confidence: 99%
“…In addition, alginates or chitosan as two natural biopolymers were used to perform natural dressings with haemostatic properties . Furthermore, the combination of biologically effective polysaccharides such as chitosan and alginic acid or carrageenan to form hydrogels applied to dressings has shown an interesting biological effect …”
Section: Introductionmentioning
confidence: 99%
“…4 Alginate possesses excellent biocompatibility, low toxicity and its derivatives (i.e., hydrogel, beads, scaffolds, and fibers) are widely used in biological materials, such as delivery system for drug, protein, or cells, wound dressings, blood vessels, tissue engineering scaffolds, and other biomaterials. [5][6][7][8][9][10][11][12][13][14] The calcium alginate fibers (CAFs) are fabricated by wet spinning process. In the process, CA nascent filaments are prepared by extruding sodium alginate (SA) solution into the coagulation solution containing a large amount of Ca 21 ions.…”
Section: Introductionmentioning
confidence: 99%